Role of tyrosine phosphorylation of a cellular protein in adeno-associated virus 2-mediated transgene expression - Qing, Keyun (The National Academy of Sciences of the USA, 1997)
The adeno-associated virus 2 (AAV), a single-stranded DNA-containing, nonpathogenic human parvovirus, has gained attention as a potentially useful vector for human gene therapy. However, the single-stranded nature of the viral genome significantly impacts upon the transduction efficiency, because the second-strand viral DNA synthesis is the rate-limiting step. We hypothesized that a host-cell protein interacts with the single-stranded D sequence within the inverted terminal repeat structure of the AAV genome and prevents the viral second-strand DNA synthesis. Indeed, a cellular protein has been identified that interacts specifically and preferentially with the D sequence at the 3′ end of the AAV genome. This protein, designated the single-stranded D-sequence-binding protein (ssD-BP), is phosphorylated at tyrosine residues and blocks AAV-mediated transgene expression in infected cells by inhibiting the leading strand viral DNA synthesis. Inhibition of cellular protein tyrosine kinases by genistein results in dephosphorylation of the ssD-BP, leading not only to significant augmentation of transgene expression from recombinant AAV but also to autonomous replication of the wild-type AAV genome. Dephosphorylation of the ssD-BP also correlates with adenovirus infection, or expression of the adenovirus E4orf6 protein, which is known to induce AAV DNA replication and gene expression. Thus, phosphorylation state of the ssD-BP appears to play a crucial role in the life cycle of AAV and may prove to be an important determinant in the successful use of AAV-based vectors in human gene therapy.